Peningkatan volume pemurnian minyak ikan tuna (Thunnus sp.) dari hasil samping pengalengan: Increased refining volume of tuna (Thunnus sp.) fish oil from canning by-products - Adenia Cahyatie Aprillia; Sugeng Heri Suseno; Bustami Ibrahim (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
The canned fish industry produces by-products such as low-quality fish oil with non-oil ingredients according to the International Fish Oil Standards (IFOS); therefore, purification must be carried out by neutralization and bleaching using centrifugation to obtain fish oil according to consumer needs. The results of previous research were generally limited to small scales of the quantity and quality of tuna oil, so its application to Micro, Small and Medium Enterprises (MSMEs) cannot be immediately adopted. This study aimed to obtain a tuna fish oil refining process that complied with IFOS standards. This study used a Completely Randomized Design (CRD) with purification volume levels (5, 7.5, and 10 L) by centrifugation at 10,000 rpm for 10 min. The test analysis included the free fatty acid (FFA) content, peroxide value (PV), p-anisidine value (p-Anv), total oxidation number (totox), clarity number, yield number, heavy metal content, and fatty acid profile. The total saturated fatty acid (SFA) content in crude tuna oil was 22.46%. Monounsaturated Fatty Acids (MUFA) accounted for 25.38%, while Polyunsaturated Fatty Acids (PUFA) accounted for 25.01%. PUFA was dominated by DHA (15.57 %), whereas EPA fatty acid content was 3.15%. The best treatment was obtained in the treatment of 10 L purification volume with oxidation parameters namely free fatty acids 0.36±0.05%, peroxide value 6.87±0.09 mEq/kg, p-anisidine value 6.28±0.1 mEq/kg; total oxidation value 20±0.29 mEq/kg, physical parameters for clarity was 91.88±0.04%, with a yield value 87±1.70%.